IMPLEMENTASI KEBIJAKAN DISIPLIN PNS PADA PEMERINTAH KECAMATAN KAO UTARA KABUPATEN HALMAHERA UTARA - KOLOLI, RUMONDANG YOS ELISABETH; PANGKEY, MASJE; LONDA, VERY (Sam Ratulangi University, 2018)
The purpose of this study is to find out how the implementation of civil servant discipline policy at theGovernment District Northern Kao North Halmahera District.This research uses quantitative approach method. Informant research is as much as 5 people PNS office ofNorth Kao Subdistrict that is Camat, Secretary of District, Section Head of PMD and two staff employee. Datawas collected using interview guidelines, while the analytical technique used was interactive model analysisfrom Miles and Hubernan.Based on the results of data analysis, the conclusions are drawn: (1) Communication or socialization for theimplementation of the policy policy of civil servants discipline done fairly well since the enactment of the civilservant discipline policy (PP.53 / 2010). (2) Resources for the implementation of civil servant discipline policyhas not been maximized but good enough seen from the ability of employees in understanding andimplementing civil servant discipline policy. (3) The disposition or characteristics possessed by the employeeshas not been maximized but already good enough in terms of willingness / commitment and consistency tocomply with obligations and restrictions stipulated in the rules of civil servants discipline. (4) The bureaucracystructure for the implementation of civil servant discipline policy is quite good seen from SOP and division ofwork / responsibility.Based on the conclusions of the results of the study, it should be mentioned some suggestions as follows: (1)The discipline policy of civil servants should continue to be communicated or socialized to employees in orderto raise awareness to implement it as well as possible. (2) The ability of human resources of employees tounderstand and implement the policy of civil servant discipline should be continuously improved throughtraining and discipline development. (3) The willingness / commitment and consistency of employees toimplement the policy discipline of civil servants properly and correctly also need to be improved throughcontinuous guidance coaching. (4) Bureaucratic structure (SOP and division of work / responsibility) must beadhered to properly by the employee, so that the application of sanctions for each violation must be done firmly.Keywords: Policy implementation, civil servant discipline